Clinical outcomes of different therapeutic options for COVID-19 in two Chinese case cohorts: A propensity-score analysis. (February 2021) - Wong, Carlos K.H.; Wan, Eric Y.F.; Luo, Sihui; Ding, Yu; Lau, Eric H.Y.; Ling, Ping; Hu, Xiaowen; Lau, Edward C.H.; Wong, Jerry; Zheng, Xueying; Cowling, Benjamin J.; Weng, Jianping; et al.
Abstract: Background: The timing of administration of agents and use of combination treatments in COVID-19 remain unclear. We assessed the effectiveness of therapeutics in cohorts in Hong Kong SAR and Anhui, China. Methods: We conducted propensity-score analysis of 4771 symptomatic patients from Hong Kong between 21st January and 6th December 2020, and 648 symptomatic patients from Anhui between 1st January and 27th February 2020. We censored all observations as at 13st December 2020. Time from hospital admission to discharge, and composite outcome of death, invasive mechanical ventilation or intensive care unit admission across 1) all therapeutic options including lopinavir-ritonavir, ribavirin, umifenovir, interferon-alpha-2b, interferon-beta-1b, corticosteroids, antibiotics, and Chinese medicines, and 2) four interferon-beta-1b combination treatment groups were investigated. Findings: Interferon-beta-1b was associated with an improved composite outcome (OR=0.55, 95%CI 0.38, 0.80) and earlier discharge (−8.8 days, 95%CI −9.7, −7.9) compared to those not administered interferon-beta-1b. Oral ribavirin initiated within 7 days from onset was associated with lower risk of the composite outcome in Hong Kong (OR=0.51, 95%CI 0.29, 0.90). Lopinavir-ritonavir, intravenous ribavirin, umifenovir, corticosteroids, interferon-alpha-2b, antibiotics or Chinese medicines failed to show consistent clinical benefit. Interferon-beta-1b co-administered with ribavirin was associated with improved composite outcome (OR=0.50, 95%CI 0.32, 0.78) and earlier discharge (−2.35 days, 95%CI −3.65, −1.06) compared to interferon-beta-1b monotherapy. Interpretation: Our findings support the early administration of interferon-beta-1b alone or in combination with oral ribavirin for COVID-19 patients. Funding: Hong Kong Health and Medical Research Fund; Hong Kong Innovation and Technology Commission; Chinese Fundamental Research Funds for the Central Universities.